2013
DOI: 10.1016/j.elecom.2012.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Formation of anodic TiO2 nanotube or nanosponge morphology determined by the electrolyte hydrodynamic conditions

Abstract: ElsevierSánchez Tovar, R.; Lee, K.; García Antón, J.; Schmuki, P. (2013) AbstractThe present work studies the effect of hydrodynamic conditions on the growth of anodic TiO 2 nanostructures on Ti in a glycerol/water/NH 4 F electrolyte. Parameter screening for fluoride content, anodization voltage and rotation rate (Reynolds number) of a rotating anode showed that two distinctly different TiO 2 morphologies could be obtained: the classic ordered nanotubes or a nanoscale sponge layer. We present conditions for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 26 publications
1
40
0
5
Order By: Relevance
“…Thus, the current density increases as the reactive area also increases [25,35]. Finally, in the third stage (stage III), current density remains almost constant due to the formation and growth of regular nanotubes [25,26].…”
Section: Current Density Transients During Anodizationmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the current density increases as the reactive area also increases [25,35]. Finally, in the third stage (stage III), current density remains almost constant due to the formation and growth of regular nanotubes [25,26].…”
Section: Current Density Transients During Anodizationmentioning
confidence: 90%
“…The latter has the advantage of removing the "initiation layer" in the same process of anodization and, therefore, other independent processes in order to remove this layer are not needed. Moreover, the use of hydrodynamic conditions can significantly affect on the final TiO 2 nanotube geometry [22,26,27]. After anodization, an amorphous structure is obtained which implies the presence of a high number of defects.…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications, the influence of hydrodynamic conditions on the anodization process has been evaluated [31], and it has been observed that under flux conditions the geometry of the formed nanostructures is different from that obtained under stagnant conditions, i.e., nanotubes. This new nanostructure, called nanosponge, provides better performance than tube morphologies, for example, for the water splitting process [31].…”
Section: Introductionmentioning
confidence: 99%
“…This new nanostructure, called nanosponge, provides better performance than tube morphologies, for example, for the water splitting process [31].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years not only TiO 2 nanotubes have been widely examined [12] but also "non-thickness limited" ordered channel layers attracted wide interest [13]. Most recently [14], another morphology, anodic nanosponge layers, were observed when using anodization with a rotating electrode configuration.…”
Section: Introductionmentioning
confidence: 99%